2004
DOI: 10.1038/ng1487
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the NESP55 differentially methylated region causes loss of maternal GNAS imprints and pseudohypoparathyroidism type Ib

Abstract: Epigenetic defects in the imprinted GNAS cluster are associated with pseudohypoparathyroidism type Ib. In two kindreds with this disorder, we now report deletions that remove the differentially methylated region encompassing exon NESP55 and exons 3 and 4 of the antisense transcript. When inherited from a female, either deletion abolishes all maternal GNAS imprints and derepresses maternally silenced transcripts, suggesting that the deleted region contains a cis-acting element that controls imprinting of the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
182
2
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(199 citation statements)
references
References 15 publications
12
182
2
3
Order By: Relevance
“…Another study identified maternally transmitted deletions of an upstream exon of the NESP55 transcript within the GNAS locus in two families, which were associated with methylation defects at all downstream GNAS ICRs located at exons AS1, XL and A/B (Figure 2 and Table 1). 63 At least some of these deletions could affect transcription of NESP55 in oocytes, which is presumed to proceed through AS1, XL and exon A/B. In light of the study on the mouse Gnas locus, 26 it is conceivable that the absence of NESP55 transcription leads to a failure in imprint establishment.…”
Section: Childhood Diseases Associated With Imprint Establishment or mentioning
confidence: 99%
“…Another study identified maternally transmitted deletions of an upstream exon of the NESP55 transcript within the GNAS locus in two families, which were associated with methylation defects at all downstream GNAS ICRs located at exons AS1, XL and A/B (Figure 2 and Table 1). 63 At least some of these deletions could affect transcription of NESP55 in oocytes, which is presumed to proceed through AS1, XL and exon A/B. In light of the study on the mouse Gnas locus, 26 it is conceivable that the absence of NESP55 transcription leads to a failure in imprint establishment.…”
Section: Childhood Diseases Associated With Imprint Establishment or mentioning
confidence: 99%
“…22 However, maternal deletions affecting AS exons 3 and 4 result in a loss of methylation at all maternal GNAS imprints. 15,23 Gross deletions affecting some or all the DMRs of GNAS locus and leading to an apparent methylation defect has also been published. [7][8][9] EQA for PHP not caused by point genetic variants I Garin et al of 20 ng of bisulphite-treated DNA, 1 Â of Megamix Gold (Microzone Ltd, Haywards Heath, UK) and 0.2 mM of primers (Life Technologies, Carlsbad, CA, USA), and 2 ml PCR products were used as template for in vitro transcription and RNAaseA cleavage for the T-reverse reaction (Sequenom hMC, San Diego, CA, USA).…”
Section: Methylation Detectionmentioning
confidence: 99%
“…In addition, deletions removing the entire NESP55 DMR as well as part of GNAS-AS transcript have also been identified in some AD-PHP1B kindreds in whom affected individuals show loss of all maternal GNAS imprints. 15,23 However, clinical and molecular analysis for PHP is not easy to achieve because of different reasons. First, beyond the classic PHP type 1 classification, our groups and others demonstrated a genetic overlap between PHP1A and PHP1B, reporting patients with mild AHO features and methylation defects.…”
Section: Introductionmentioning
confidence: 99%
“…PHP-Ib patients display methylation abnormalities in the GNAS differentially methylated regions, such as NESP hypermethylation versus XL/Nespas and Exon A/B hypomethylation. 2 Familial cases of PHP-Ib present with Exon A/B-only hypomethylation 3,4 that appears to be caused by maternally inherited deletions affecting imprinting control centers in either the STX16 gene 5,6 or the NESP55/NESPAS region. 2,7 Paternal Gsalpha-inactivating mutations lead to pseudopseudohypoparathyroidism (PPHP).…”
mentioning
confidence: 99%
“…2 Familial cases of PHP-Ib present with Exon A/B-only hypomethylation 3,4 that appears to be caused by maternally inherited deletions affecting imprinting control centers in either the STX16 gene 5,6 or the NESP55/NESPAS region. 2,7 Paternal Gsalpha-inactivating mutations lead to pseudopseudohypoparathyroidism (PPHP). 1,8,9 This clinical condition is characterized by highly variable AHO features but no hormone resistance.…”
mentioning
confidence: 99%